THE INFLUENCE OF RELIGIOUS GROUPS ON LGBT POLICIES IN THAILAND AND INDONESIA FROM A HUMAN RIGHTS PERSPECTIVE - Nurhayati Nur; Khoirunnisa (Jurnal Humaniora & Sosial Sains, 2025)
This research examines the influence of religious groups on LGBT policies in Thailand and Indonesia from a human rights perspective, focusing on the differences in policy implementation influenced by religious values in the two countries. This research uses a qualitative approach with descriptive-analytical methods. Data was collected through a literature study that included academic journals, legal documents, and international organization reports. The results show that in Thailand, Buddhism's emphasis on tolerance has led to relatively inclusive policies towards the LGBT community, although structural discrimination remains in some aspects. In contrast, in Indonesia, the influence of conservative Islamic groups is dominant, resulting in more restrictive policies towards the LGBT community, with significant social and political pressure. The research also found that human rights principles have not been fully integrated into LGBT policies in either country, although Thailand tends to be more open to change. As such, this research contributes to understanding the dynamics between social norms, conservative religious values, and human rights principles and the implications for LGBT-related policy formation in two countries with very different cultural backgrounds.